De Garengeot's hernia: our experience of three cases and literature review. (30th July 2014) - Akbari, Khalid; Wood, Claire; Hammad, Ahmed; Middleton, Simon
Abstract : Groin hernia is a common surgical presentation and nearly half of the femoral hernias present acutely with strangulation. The hernia sac usually contains omentum or small bowel. Rarely, the appendix can herniate into the femoral canal. De Garengeot's hernia is the term used to describe the presence of appendicitis in the femoral hernia. Hernia explorations are performed by surgical trainees and encountering a De Garengeot's hernia can be challenging to manage. We report our experience of three cases of this rare entity and a literature review to improve our understanding for optimum management.